'Words are like weapons, they wound sometimes': Andrew Bolt, gay white men, and an out and proud gay black man - Mark McMillan (2015)
This book uncovers the often hidden world of Queer and Trans Blak Australia and tells it like it is. Twenty-two First Nations people reveal their inner reflections and outlooks on family and culture, identity and respect, homophobia, transphobia, racism and decolonisation, activism, art, performance and more, through life stories and essays.